Tectonic Evolution of the Southern Negros Geothermal Field and Implications for the Development of Fractured Geothermal Systems. (19th November 2018) - Pastoriza, Loraine R.; Holdsworth, Robert E.; McCaffrey, Kenneth J. W.; Dempsey, Edward
Abstract : Fluid flow pathway characterisation is critical to geothermal exploration and exploitation. In fractured geothermal reservoirs, it requires a good understanding of the structural evolution together with the fracture distribution and fluid flow properties. A fieldwork-based approach has been used to evaluate the potential fracture permeability characteristics of a typical high-temperature geothermal reservoir in the Southern Negros Geothermal Field, Philippines. This is a liquid-dominated resource hosted in the andesitic Quaternary Cuernos de Negros Volcano, Negros Island. Fieldwork reveals two main fracture groups based on fault rock characteristics, alteration type, relative age of deformation, and associated thermal manifestation, with the youngest fractures mainly related to the development of the current geothermal system. Fault kinematics, cross-cutting relationships, and palaeostress analysis suggest at least two distinct deformation events under changing stress fields since probably the Pliocene. We propose that this deformation history was influenced by the development of the Cuernos de Negros Volcano and the northward propagation of a major neotectonic structure located to the northwest, the Yupisan Fault. A combined slip and dilation tendency analysis of the mapped faults indicates that NW-SE structures should be particularly promising drilling targets under the inferred current stress regime, consistent with drilling results. However, existing boreholes also suggest that NE–SW structures can act as effective channels for geothermal fluids. Our observations suggest that these features were initiated as the dominant features in the older kinematic system and have then been reactivated at the present day.